Expression of oestrogen receptor, androgen receptor and progesterone nuclear receptor in sheep uterus during the oestrous cycle. Issue 10 (1st August 2019) - Duan, Hongwei; Xiao, Longfei; Hu, Junjie; Zhang, Yong; Zhao, Xingxu; Ge, Wenbo; Jiang, Yuting; Song, Liangli; Yang, Shanshan; Luo, Wenze
Abstract: Oestrogen, androgen and progesterone are involved in the regulation of uterine physiological functions, with the participation of the following proteins: oestrogen receptor (ER), androgen receptor (AR) and progesterone nuclear receptor (PGR). In this study, we used immunohistochemistry to detect the localization of ERα, ERβ, AR and PGR in sheep uterus. Additionally, we used real‐time polymerase chain reaction (RT‐qPCR) and Western blot technique to analyse their expression profiles at different stages of sheep oestrous cycle in the endometrium and myometrium. Immunohistochemical analysis showed that ERα, ERβ, AR and PGR were present in sheep uterus in oestrus, mainly in the uterine luminal epithelium, stroma, gland and myometrium. Real‐time polymerase chain reaction results showed that in the endometrium, ERα expression level was highest in oestrus. ERβ and PGR, instead, were highly expressed in pro‐oestrus. In the myometrium, ERα was highly expressed in both oestrus and pro‐oestrus, and ERβ was highly expressed in oestrus and dioestrus. Progesterone nuclear receptor expression was highest in oestrus, followed by metoestrus. In the endometrium, both receptors ERα and ERβ were abundant in pro‐oestrus, while the maximum AR protein content was found in oestrus. At this stage of the oestrous cycle, PGR protein concentration in the myometrium was significantly lower than those observed in other stages. These results suggest that these receptors are important for sheep reproductive function, as their expression at mRNA and protein levels exhibits particular time‐ and tissue‐specific profiles along the oestrous cycle.